Recent Advances of Marine Natural Indole Products in Chemical and Biological Aspects - Haoyi Sun; Kangping Sun; Jingyong Sun (Molecules, 2023)
The ocean has always been one of the important sources of natural products. In recent years, many natural products with different structures and biological activities have been obtained, and their value has been clearly recognized. Researchers have been deeply engaged in the field of separation and extraction, derivative synthesis, structural studies, biological evaluation, and other fields of research for marine natural products. Thus, a series of marine indole natural products which have structural and biological prospect have caught our eyes. In this review, we summarize some of these marine indole natural products with relatively good pharmacological activity and research value, and discuss issues concerning chemistry, pharmacological activity, biological evaluation, and synthesis, including monomeric indoles, indole peptides, bis-indoles, and annelated indoles. Most of the compounds have cytotoxic, antiviral, antifungal, or anti-inflammatory activities.